1979
DOI: 10.1093/bja/51.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Etomidate on Intracranial Pressure and Cerebral Perfusion Pressure

Abstract: Ten patients with intracranial lesions, anaesthetized with thiopentone and nitrous oxide (70%) in oxygen (30%) received etomidate 0.2 mg kg-1 i.v. Ventilation was controlled in each patient. Intracranial pressure (i.c.p.) and mean arterial pressure (m.a.p.) were recorded. I.c.p. decreased significantly in all patients (0.01 greater than P greater than 0.001). Although PaCO2 decreased during the period of measurement, the extent and time-course of this change suggested that it was not mainly responsible for cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…It is considered the most hemodynamically neutral induction agent of all commonly used induction agents and a drug of choice for patients with elevated ICP [13,14].…”
Section: Etomidatementioning
confidence: 99%
“…It is considered the most hemodynamically neutral induction agent of all commonly used induction agents and a drug of choice for patients with elevated ICP [13,14].…”
Section: Etomidatementioning
confidence: 99%
“…In 1979, Moss and colleagues demonstrated the efficacy of etomidate in causing a significant ICP reduction with a minimal reduction in MAP and CPP [39]. Similarly, in pediatrics, Bramwell and colleagues demonstrated that a single dose of etomidate is effective at reducing ICP while maintaining MAP and CPP [40].…”
Section: Contraindications Hypersensitivitymentioning
confidence: 99%
“…Etomidate also exhibits neuroprotective effects by reducing intracranial pressure (ICP). [15] However, etomidate can cause hypotension, especially in the critically-ill and under-resuscitated patient such as most emergent trauma patients. We recommend having vasopressor agents ready if needed to treat peri-intubation hypotension.…”
Section: Airway Managementmentioning
confidence: 99%